Evidences of Rock shags (Phalacrocorax magellanicus) and Imperial cormorants (Ph. atriceps) leaving their nest by night - Sapoznikow, Alexandra; Quintana, Flavio Roberto
Imperial Cormorants Phalacrocorax atriceps and Rock Shags P. magellanicus are foot-propelled pursuit divers usually described as visual feeders (Johnsgard 1993). Previous studies describing Imperial Cormorant and Rock Shag feeding behaviour show that birds forage from dawn to dusk (Croxall et al. 1991, Quintana 1999, 2001). Fil: Sapoznikow, Alexandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos